2020
DOI: 10.1111/flan.12467
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling for the foreign language classroom

Abstract: At a time when many language teachers are looking for research-based teaching materials that can be modified to support their students in online or digital learning, existing teaching and assessment materials developed through European grant-funded projects can provide valuable and ready-to-use resources. This paper reports on the published and forthcoming teaching materials developed by the FanTALES group for teaching multilingual interactive digital storytelling to low-to-high intermediate level learners, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Interestingly, a few studies describe the role of IF in teaching a foreign language. One article describes the development of specific IF writing prompts for multilingual students to utilize as part of their foreign language curriculum (Sauro et al, 2020). Another study provides a real-world account of this pedagogical intervention in a secondary English class in Belgium, concluding that there were many challenges with the open-ended aspects of the project and students lacking prior storytelling knowledge-but ultimately students benefitted in terms of developing domain-specific skills in language (Cornillie et al, 2021).…”
Section: If As a Creative Writing Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a few studies describe the role of IF in teaching a foreign language. One article describes the development of specific IF writing prompts for multilingual students to utilize as part of their foreign language curriculum (Sauro et al, 2020). Another study provides a real-world account of this pedagogical intervention in a secondary English class in Belgium, concluding that there were many challenges with the open-ended aspects of the project and students lacking prior storytelling knowledge-but ultimately students benefitted in terms of developing domain-specific skills in language (Cornillie et al, 2021).…”
Section: If As a Creative Writing Mediummentioning
confidence: 99%
“…These two statements may indicate the potential of the text adventure as an introductory activity that leads a "tinkerer" into an eventual career as a computer programmer. Felnhofer et al, 2022;Gómez-Albarrán et al, 2021;Sarasa-Cabezuelo, 2020;Sauro et al, 2020).…”
Section: Second Games Development Was a Core Pathway Into Professiona...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have examined how digital devices facilitate students' reading and listening skills, oral proficiency or motivation in learning a second or additional language (Brevik & Davies, 2016; Tai & Wei, 2021). Other studies have addressed students' digital skills in the L2 English subject using new genres, like blogs and wikis (Lund, 2003), fan fiction (Sauro et al, 2020; Sauro & Sundmark, 2019) and language learning through immersion in game‐based virtual worlds (Brevik & Holm, 2022; Sykes, 2018; Zheng et al, 2009). Additionally, studies have demonstrated new uses of traditional tools in L2 English lessons, like iPads for speaking practice in language classes (Lys, 2013), monolingual online dictionaries, thesauruses, machine translation services (Beiler & Dewilde, 2020) and digital storytelling (Normann, 2012).…”
Section: Students' Opportunities For English Digital Skill Usementioning
confidence: 99%
“…Per questa ragione, per far leva sulla motivazione e le emozioni degli allievi in aula, le immagini e le storie della moda possono rappresentare utili strumenti per innescare e/o favorire il processo di acquisizione della lingua. La definizione di storytelling, spiega Diadori, compare in letteratura alla fine del XX secolo e consiste nell'idea che le narrazioni facilitino la memorizzazione dei contenuti disciplinari e possano anche consentire l'interazione sociale sia nel contesto classe tradizionale (Fiorentino et al, 2015;Sauro et al, 2020), in quello digitale (Brichese, 2014;Pezzot, 2016;Nami, 2020) che fuori. Vari possono essere inoltre i generi testuali e i task da proporre attraverso la narrazione di storie, a testimonianza di quanto duttile sia lo strumento.…”
unclassified